2014
DOI: 10.1038/ismej.2014.242
|View full text |Cite|
|
Sign up to set email alerts
|

The host metabolite D-serine contributes to bacterial niche specificity through gene selection

Abstract: Escherichia coli comprise a diverse array of both commensals and niche-specific pathotypes. The ability to cause disease results from both carriage of specific virulence factors and regulatory control of these via environmental stimuli. Moreover, host metabolites further refine the response of bacteria to their environment and can dramatically affect the outcome of the host-pathogen interaction. Here we demonstrate that the host metabolite, D-serine, selectively affects gene expression in E. coli O157:H7. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(101 citation statements)
references
References 60 publications
(99 reference statements)
2
98
1
Order By: Relevance
“…Previous work by our group identified D-serine as an important niche-specific signal that is involved in the regulation of the infection process by repressing the EHEC T3SS essential for colonization of the host (31). Transcriptomic analysis showed that exposure to millimolar concentrations of D-serine (similar to those found in the urinary tract) also resulted in upregulation of the SOS response regulon, and this was dependent on D-serine accumulation independently of T3SS repression.…”
Section: Intracellular Accumulation Of D-serine Increases Reca Producmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous work by our group identified D-serine as an important niche-specific signal that is involved in the regulation of the infection process by repressing the EHEC T3SS essential for colonization of the host (31). Transcriptomic analysis showed that exposure to millimolar concentrations of D-serine (similar to those found in the urinary tract) also resulted in upregulation of the SOS response regulon, and this was dependent on D-serine accumulation independently of T3SS repression.…”
Section: Intracellular Accumulation Of D-serine Increases Reca Producmentioning
confidence: 87%
“…As a control, whole-cell lysates were also probed with anti-DnaK antibody to demonstrate normalized total protein levels and equal loading of the lanes. This indicates that this SOS response is unique to D-serine, as was the repression of the EHEC T3SS (31). D-Serine-induced RecA production does not activate lysogenic stx phages.…”
Section: Intracellular Accumulation Of D-serine Increases Reca Producmentioning
confidence: 93%
See 3 more Smart Citations